KEWENANGAN BIDAN DALAM MELAKUKAN METODE PERSALINAN GENTLE BIRTH PADA IBU BERSALIN MELALUI PENDEKATAN HOLISTIC CARE - Karlina Sumiari Tangkas; Indrie Lutfiana (STIKes Buleleng, 2018)
ABSTRACT Introduction: Complementary and traditional health services are currently global issues, which are contained in the 2014-2023 World Health Organization strategy related to complementary alternative medicine. The manifestation of complementary services can be seen from the practice of gentle birth which is currently the choice of maternity to gain security, nayman and reduced pain where a holistic approach is used in practice. But there is still a difference of views on this method into a complex problem to be discussed. For this reason, discussion is needed regarding the authority of midwives in gentle birth practices through a holistic care approach so that midwives receive legal protection. The purpose of this study is to examine the authority of midwives in carrying out gentle birth through a holistic care approach. Method: The method used is a qualitative research method with descriptive phenomenological design. There were 7 respondents in the study selected using purposive sampling sampling techniques based on inclusion criteria. Data is collected through interview techniques. Results: The results obtained include the implementation of gentle birth practices that support care for mothers and babies through a holistic care approach, and the authority of midwives is regulated in legislation, professional standards, minimum service standards, and midwives' code of ethics. This authority is a form of legal protection for midwives. Conclusion: The conclusion that can be drawn from this study is that midwives have authority in the delivery assistance with gentle birth method and through a holistic care approach is the challenge of midwives in carrying out care where this method is an old way with new terms. Keywords: authority, midwife, gentle birth, holistic care